Treatment of Mixer Truck Wash Water of a Ready-mix Concrete Batching Plant Using a Low Cost Modified Sand Filter: Pengolahan Air Cucian Truk Mixer Pabrik Beton Siap Pakai Menggunakan Modifikasi Filter Pasir Berbiaya Rendah - YENNI CIAWI; I PUTU GUSTAVE SURYANTARA PARIARTHA; AYUB BENNY KRISTIANTO (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2022)
ABSTRAK Pembangunan infrastruktur dan perumahan membutuhkan beton dalam jumlah besar, yang sebagian dipasok oleh pabrik beton siap pakai. Tingginya kebutuhan air dan produksi air limbah oleh industri ini menyebabkan masalah lingkungan yang signifikan. Sebuah pabrik beton di Bali mengolah air limbahnya dengan lima kolam sedimentasi sederhana yang dilengkapi dengan saringan ijuk antar kolam dan kemudian air hasil olahan dibuang ke hutan bakau di sekitarnya. Meskipun nilai Chemical Oxygen Demand (COD) telah diturunkan dari 316,149 mg/L menjadi 146 mg/L, air limbah ini masih berpotensi merusak biota hutan bakau. Padahal, air bisa didaur ulang untuk membersihkan peralatan atau bahkan menjadi air proses. Penelitian ini bertujuan merancang proses pengolahan yang sederhana dan murah beserta peralatannya. Air limbah yang berasal dari bak pengendapan di pabrik beton siap pakai diolah di laboratorium menggunakan tawas tetapi hasilnya tidak memuaskan sehingga dipilih metode fisika dengan menggunakan kolam sedimentasi dan saringan pasir lambat yang dimodifikasi, dan berhasil menurunkan nilai COD sebesar 82,83% pada pH 12,27 dan mendaur ulang 84% air limbah atau 26,7% kebutuhan air total industri ini. Kata kunci: pengolahan air limbah, beton siap pakai, desain bangunan, daur ulang air ABSTRACT Infrastructure and housing developments require vast quantities of concrete, which are supplied by the ready-mix concrete (RMC) batching plant. This industry's high water demand and wastewater generation have caused significant environmental problems. An RMC batching plant in the southern part of Bali produces liquid waste, which is disposed of into the surrounding mangrove forests after being treated using five sequential unlined wash water ponds and palm fibre. Although the COD value has been decreased from 316.149 mg/L of untreated wastewater to 146 mg/L after treatment, this still has the potential to harm the mangrove biota. On the other hand, the water can still be reclaimed for cleaning purposes or even incorporated into process water. The work aims to design a low cost and simple wastewater recycling process and equipment. Wastewater was collected from the existing settling basin at the RMC batching plant and treated in the laboratory. It was found that the chemical treatment of wastewater using alum did not produce satisfactory results; therefore, a physical method was chosen by employing a sedimentation pond and a modified slow sand filter. It removed 82.83% of the COD at pH 12.270 and reclaimed 84% wash water or 26.7% of total water needed for this industry. Keywords: wastewater treatment, ready-mix concrete, building design, water recycles